BIMBINGAN KELOMPOK TEKNIK PERMAINAN SIMULASI UNTUK MENINGKATKAN KERJASAMA DALAM BELAJAR SISWA SD - Asmarani, Indira Restu; Asrowi, Asrowi; Muslim, Mudaris (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2016)
The aim of this research was to create game simulation which appropriate and effective as media development of group counseling model through simulation game technique to improve students? team work in study at fifth grade of elementary school. This was a Research and Development. The result of analysis showed that test result index from Test of Interrater agreement Model was 1.00, it could be concluded that guidance book assessment by two experts had very good validity with almost perfect agreement level, it meant two experts gave same scoring to the simulation game technique product. The result of the test was supported by treatment result that was tcount 7.823 and ttable 1.69552, it meant the hypothesis was proven. The conclusion of this research was group counseling model through simulation game technique was effective to improve students? team work in study at fifth grade of elementary school.